Intraoperative radiotherapy during kyphoplasty (Kypo-IORT): a novel treatment approach for patients with symptomatic spinal metastases - Reis, Tina; Sperk, Elena; Schneider, Frank; Bludau, Frederic; Obertacke, Udo; Wenz, Frederik (Translational cancer research, 2015)
Palliation like pain reduction, stabilization and local control are main treatment goals for patients with spinal metastases. To shorten treatment and reduce hospitalization time, various novel therapy approaches like stereotactic body radiotherapy (SBRT) with single high-doses or minimally invasive surgical techniques (e.g., kyphoplasty) combined with other physical method are increasingly used. Intraoperative radiotherapy combined with kyphoplasty (Kypo-IORT) is an X-ray based approach using the Intrabeam ® system. It is a technically feasible therapy method with immediate pain relief and excellent local tumor control. In our recently closed dose escalation study a dose of 8 Gy in 13 mm depth from isocenter of the radiation source was determined as the maximally tolerated dose and will be tested in a phase III study.